PENINGKATAN KONSENTRASI BELAJAR PADA ANAK MELALUI BERMAIN SENSORIMOTOR - Yuniarti; Tia Larasati; Diana (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2023)
This research is motivated by children who are less able to concentrate when learning activities take place. This is addressed by children with indifferent attitudes during learning. The child pays little attention to the teacher speaking in front of the class, when the teacher asks to complete activities such as stacking blocks or sticking leaves on a picture book the child cannot complete it, and the child also does not want to do the activities given by the teacher, when the learning activity takes place the child only able to concentrate for 5-7 minutes because the attention is often changing to do activities that children prefer. The purpose of this study was to determine the planning, implementation, and results of increasing children's learning concentration through sensorimotor play. The indicators in this study are to recognize rough, smooth, and slippery textures. This research method uses a descriptive qualitative approach to class action research. The research subjects were 32 children with an age range of 4-5 years. Data collection tools using observation guidelines, interview guides, and documentation. The results of this study showed that the research subjects experienced an increase in learning concentration of 80% in the very well-developed criteria for each assessment indicator. The indicators for recognizing coarse textures achieved very good results of 83.03%, the indicators for recognizing smooth textures reached 88.08%, and the indicators for recognizing smooth textures reached 88.08%. The results of the research show that planning is carried out by compiling learning designs, determining learning objectives, designing media, RPPH, and room arrangement. The process of carrying out sensorimotor children touches the surface of the skin of fruits to recognize rough and fine textures. Meanwhile, to get to know the slippery texture, the teacher peels the skin of the fruit which is then touched by the child. Sensorimotor play can be used as a learning activity to improve children's learning concentration. The result of sensorimotor games is that children are trained to follow rules, and wait their turn so that children are more organized and help improve children's learning concentration.